Pengaruh Bauran Pemasaran Ritel Terhadap Minat Beli Konsumen (Studi Kasus Pada Santri Mart Tebuireng Jombang) - Hanin Hanifah; Tri Sudarwanto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to determine the influence of retail baseline marketing toward consumer interest in Santri Mart Tebuireng. This type of the study is verification or quantitative study. The populations in this study were 70 respondents. The number of the samples were 70 respondents by using multiple resresi linear analysis. This study was used descriptive quantitative and statistical analysis which was to determine direct and indirect relationship between the retail baseline marketing variable. The result derived from location variables affect toward consumer interest directly. Product variables affect toward consumer interest directly. Price variables affect toward consumer interest directly. Promotion variables affect toward consumer interest directly. Atmosphere variables affect toward consumer interest directly. And retail service variables affect toward consumer interest directly to the Santri Mart Tebuireng. Keywords: Location; Product; Price; Promotion; Atmosphere; Retail Service Consumer Interest